Pilot evaluation of a rapid immunochromatographic test for the diagnosis of gestational syphilis - Ramos, Mauro Cunha; Bernardi, Luiz Eduardo; Silva, Marcia Susana Nunes da; Rossetti, Maria Lucia Rosa (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: Gestational syphilis is a global public health problem and one of the most common causes of adverse effects during pregnancy due to absence or inadequacy of treatment. Establishing a diagnosis of syphilis during prenatal care prevents the transmission of Treponema pallidum to the child. Objective: The objective of this study was to evaluate the performance of OL Syphilis (OrangeLife, Brazil), a rapid immunochromatographic test for gestational syphilis diagnosis. Methods: A total of 185 pregnant women in prenatal care were evaluated by OL Syphilis. The results were compared by traditional methods: Venereal Disease Research Laboratory and Rapid Plasma Reagin (VDRL and RPR) for screening and fluorescent treponemal antibody absorption test (FTA-Abs) for confirmation. Results: The prevalence of syphilis in this population was 6.49% (95%CI 3.40 to 11.06%). Rapid Test (RT) sensitivity was 91.67% (95%CI 61.52 to 99.79%) and specificity was 100% (95%CI 97.89 to 100%). Positive predictive value was 100% (95%CI 71.51 to 100%) and Negative predictive value was 99.43% (95%CI 96.84 to 100%). The agreement measured by Kappa coefficient was 0.954 (95%CI 0.863 to 1.000). Conclusion: The OL Syphilis test could be used for screening pregnant women, thus providing rapid diagnosis, increasing the probability of diagnosis and timely treatment, and preventing the devastating consequences of congenital syphilis.